Insights and Influencers: A Decade of Social Media Marketing Research Revealed Through Bibliometrics - Ahmad Khraiwish; Ahmad H. Alsharif (Scientific Annals of Economics and Business)
Social media marketing employs channels like Twitter, Facebook, Instagram, and YouTube for purposes such as advertising, customer interaction, sales, and fostering connections with the target audience. A notable gap in prior research within the Scopus database prompted this investigation, employing a bibliometric analysis focused on “(social media marketing OR social media strategy OR social media management OR social media platforms OR social media trends or social media contest OR social media analytics).” Adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, we scrutinized relevant articles on Scopus from 2013 to November 2023, revealing insights from 1,198 articles. The review findings demonstrate that the number of articles devoted to the study of social media and social media marketing has increased exponentially in recent years. More importantly, the research identifies some of the most influential studies in this area. The paper discusses trends and highlights the challenges related to social media platforms and marketing. To the authors’ knowledge, this represents the first study to review the literature from leading journals on social media platforms in marketing using bibliometric techniques. Furthermore, lays the foundation for future research, guiding scholars to less-explored areas and fostering potential collaborations, thereby enhancing the depth of understanding in this domain.